The Relationship between Optimism and Stress Levels in Compiling Final Projects for STIKES Banyuwangi Nursing Undergraduate Students in 2023: Hubungan Optimisme Dengan Tingkat Stres Dalam Menyusun Tugas Akhir Pada Mahasiswa S1 Keperawatan Stikes Banyuwangi Tahun 2023 - Fransiska Erna Damayanti; Graceila Oktamanicka Dayu; Sholihin . (Jurnal Keperawatan Malang, 2023)
ABSTRACT Background: Everyone in their lives has experienced stress, especially final-semester students who are struggling with the process of working on a thesis, which can be complicated. This situation can impact their self-confidence or ability to think positively and also affect the completion of their tasks. Optimistic thinking is needed by students because it is a psychological construct that has a positive influence on the life of an individual Purpose: This study aimed to determine the relationship between optimism and stress levels in compiling final assignments for undergraduate nursing students at STIKES Banyuwangi in 2023. Methods: This study used a cross-sectional design. The sample of this study was 43 final year STIKES Banyuwangi students using the total sampling technique. Data were collected using the Optimism and DASS 21 questionnaires and then analyzed using the Spearman rank test with SPSS 25 for windows. Results:The majority of students, 25 (58.1%), experienced normal stress levels, and most students, 26 (60.4%), had moderate optimism. Based on the analysis, a significance (2-tailed) p-value = 0.039 with ? = 0.05 was obtained, indicating that there is a low correlation between stress levels and optimism experienced by undergraduate nursing students in completing the final assignment Conclusion: Optimism is needed for students working on their final project. Through optimistic thoughts, students can reduce the impact caused by stress when working on the finalproject. Thus, individuals will respond reasonably to stress and can complete the final project well Keywords: Optimism, stress level, Final Assignment